PENGARUH BIAYA PROMOSI DAN TIKET ONLINE TERHADAP VOLUME PENJUALAN PADA PT PELNI (PERSERO) CABANG PAREPARE - Kadir, Abdul (Universitas Muhammadiyah Parepare, 2018)
This research aims to Determine The Effect Of Promotioncosts And Online Tickets On Sales Volume At PT. PELNI (Persero) Parepare Branch. This research was conducted with the aim to determine the growth of promotion costs during 2011-2015 and the growth rate of online ticket sales during 2010-2015 and to determine the effect of promotion cost and ticket sales online on the volume of ticket sales at PT. PELNI (Persero) Parepare Branch. This research is expected to be a source of scientific studies in the field of accounting and can be an input for the PT. PELNI (Persero) Parepare Branch. This research was conducted at PT. PELNI (persero) Parepare Branch. This research method is quantitative research. The independent variables in this study are promotion costs (X1) and online sales (X2) with the dependent variable is the sales volume (Y). Data collection techniques used in this research are observations, namely direct observation of the object of research; documentation, namely collecting documents relating to research; and interviews, namely conducting question and answer to parties related to this research.